Safeguarding Transactional Data: A Comprehensive Investigation of VPN Integration in Point-of-Sale Systems for Enhanced Security and Connectivity - Damasco Jr., Loreto B.; Lacson, Noel Raymund F.; Intong, Roger T. (Eximia, 2023)
The integration of Virtual Private Network (VPN) technology into Point-of-Sale (POS) systems has emerged as a solution for securing transactional data in businesses. This study investigates the implementation of a VPN server to address security and connectivity challenges faced by the University of St. La Salle (USLS) Bookstore. The research delves into VPN policy frameworks, assessing the scope and binding, authentication methods, and VPN credentials and security protocols. The system design employs a combination of conceptual models and activity diagrams to illustrate the process of user authentication and data encryption. Furthermore, the study evaluates the system’s performance in terms of scalability, efficiency, and effectiveness in ensuring authentication and security. The deployment of the VPN infrastructure involves the installation of requisite software and hardware components, along with rigorous testing procedures to assess system performance and reliability. The findings highlight the significance of VPN in safeguarding sensitive transaction data and enhancing the efficiency of POS operations. The study’s outcomes offer valuable insights into the effective implementation and management of VPN technology for securing business operations.